Study of p53 expression and post‐transcriptional modifications after GSM‐900 radiofrequency exposure of human amniotic cells1. Issue 1 (5th July 2012) - Bourthoumieu, Sylvie; Magnaudeix, Amandine; Terro, Faraj; Leveque, Philippe; Collin, Alice; Yardin, Catherine
Abstract The potential effects of radiofrequency (RF) exposure on the genetic material of cells are very important to determine since genome instability of somatic cells may be linked to cancer development. In response to genetic damage, the p53 protein is activated and can induce cell cycle arrest allowing more time for DNA repair or elimination of damaged cells through apoptosis. The objective of this study was to investigate whether the exposure to RF electromagnetic fields, similar to those emitted by mobile phones of the second generation standard, Global System for Mobile Communications (GSM), may induce expression of the p53 protein and its activation by post‐translational modifications in cultured human cells. The potential induction of p53 expression and activation by GSM‐900 was investigated after in vitro exposure of human amniotic cells for 24 h to average specific absorption rates (SARs) of 0.25, 1, 2, and 4 W/kg in the temperature range of 36.3–39.7 °C. The exposures were carried out using a wire‐patch cell (WPC) under strictly controlled conditions of temperature. Expression and activation of p53 by phosphorylation at serine 15 and 37 were studied using Western blot assay immediately after three independent exposures of cell cultures provided from three different donors. Bleomycin‐exposed cells were used as a positive control. According to our results, no significant changes in the expression and activation of the p53 protein by phosphorylation at serine 15 and 37 were found following exposure to GSM‐900 for 24 h at average SARs up to 4 W/kg in human embryonic cells. Bioelectromagnetics 34:52–60, 2013. © 2012 Wiley Periodicals, Inc.